Penerapan Strategi Pembelajaran Berbantuan YouTube untuk Meningkatkan Minat dan Pemahaman Belajar Siswa dalam Mata Pelajaran Geografi di SMAN 4 Singaraja - Emiya Ngalemisa Br Ginting; I Gede Astra Wesnawa; I Putu Ananda Citra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of a YouTube-assisted learning strategy in Geography learning, examine students' learning interest and comprehension, and investigate the effect of using YouTube as a learning medium on students' learning interest and comprehension. This study employed a quantitative approach using an experimental method. Data were collected through a learning interest questionnaire and pretest–posttest tests to measure students' comprehension. The results indicate that the implementation of the YouTube-assisted learning strategy was categorized as good. Students' learning interest and learning comprehension both improved after the implementation of the strategy. Data analysis further revealed that the YouTube-assisted learning strategy had a positive effect on students' learning interest and comprehension. Therefore, it can be concluded that the YouTube-assisted learning strategy is effective in improving students' learning interest and comprehension in Geography. The findings of this study are expected to serve as a reference for teachers in developing more engaging and interactive learning innovations.